2022
DOI: 10.1007/s42452-022-05163-0
|View full text |Cite
|
Sign up to set email alerts
|

A facile method for synthesis rGO/Ag nanocomposite and its uses for enhancing photocatalytic degradation of Congo red dye

Abstract: The enhancing breakdown of dyes using facile, novel and eco-friendly photocatalyst without remaining any hazards secondary intermediates from the dye species regarded one of the most challenges to the healthy world. A novel facile method was used to synthesize reduced graphene oxide (rGO) with various doping ratios of silver nanoparticles (Ag NPs) and applied as photocatalyst to enhancing removal of Congo red (CR) dye using UV light irradiation from aqueous solution. Some characterization features such as UV-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…At higher pH (pH > 7), there is a high generation of OH ions that facilitate the breakdown of CR molecules, thereby decreasing the removal efficiency. Similar pH-dependent results were reported for the adsorption of CR on carbon-based silver nanocomposites [55]. Hence, pH 6.5 was chosen for all other adsorption experiments with Cu 2+ , Pb 2+ , and CR dye.…”
Section: Effect Of Phsupporting
confidence: 52%
“…At higher pH (pH > 7), there is a high generation of OH ions that facilitate the breakdown of CR molecules, thereby decreasing the removal efficiency. Similar pH-dependent results were reported for the adsorption of CR on carbon-based silver nanocomposites [55]. Hence, pH 6.5 was chosen for all other adsorption experiments with Cu 2+ , Pb 2+ , and CR dye.…”
Section: Effect Of Phsupporting
confidence: 52%
“…The researchers also found that the removal efficiency improved with rising concentrations of silver NPs. Another study by Ali et al [234] investigated the use of silver nanoparticles in removing Congo red dye from water. The researcher testified that nanoparticles were successfully eliminated from the dye, with a removal efficiency of up to 98%.…”
Section: Dye Removalmentioning
confidence: 99%